Women's Multiple Roles and Social Pressure in Agrarian Society - Candra Nuraini; Abdul Mutolib (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2022)
Since 1960, the transmigration program between Java Island and Lampung Province has been massive. Some of the transmigration players are impoverished farmers seeking fresh farmland. The financial conditions of transmigrants motivate women to work in both the domestic and productive sectors. This study aims to determine women's roles and the effect of social pressure on women's roles in the agricultural region of the transmigration area in Pringsewu Regency, Lampung Province. The study was performed between November 2021 and March 2022. The research employed a qualitative case study approach. Forty respondents serve as both housewives and productive agricultural workers. The results of the study indicate that women in the Pringsewu transmigration area have three roles: housewife (domestic work), productive work (farming), and social work. Women play these equivalent roles as men in agricultural work. Women who do not engage in productive work (farming) are considered unproductive among their family and neighbors who make up stories about them. In agrarian societies in transmigration areas, a low level of education encourages the persistence of inequality. To achieve gender equality, numerous stakeholders must collaborate and maintain their efforts, particularly in agricultural communities in transmigration areas.